Gross Morphological and Morphometrical Studies on the Mandible of Adult Broiler Chicken (Gallus domesticus) - Sathapathy, S.; Sahu, S. K.; Dahariya, N.; Biswal, S. S.; Joshi, S. K. (International Journal of Livestock Research, 2020)
The present gross morphological and morphometrical study was conducted on the mandible of ten healthy adult broiler chicken collected immediately after slaughter from the local market of Bhubaneswar, Odisha. It was found that each mandible of chicken consisted of five segments as pars articularis or mandibular condyle with medial curved process, pars supraangularis, pars angularis, splenial and dentary. At the anterior aspect, the dentaries of opposite sides fused with each other forming mandibular symphysis. The right mandibular condyle was much longer cranio-caudally, whereas the left one was comparatively wider transversely at the cranial and middle regions. The left curved process was comparatively longer than the right one. The width of the curved processes decreased progressively from base towards the apex. The coronoid processes were almost equal in size. The left and right pars angularis were almost of similar lengths. The right pars angularis was thicker than the left one at the cranial and caudal aspects, but they were equally thick in the middle. Both the mandibular foramina were wider apart towards the caudal aspect than the middle and cranial regions. The left splenial was comparatively longer than the right one. Both the splenials were almost similar in thickness. The right dentary was comparatively longer and less wide than the left one. The width of the mandibular symphysis increased progressively towards the caudal aspect.